ENSURING FOOD SECURITY UNDER SANCTIONS PRESSURE - M. K. Ashinova; S. K. Yeshugova; G. V. Kadakoeva (Новые технологии)
The relevance of the research has been substantiated. Russia is under unprecedented external pressure from a wide range of economic sanctions. The agricultural sector is particularly vulnerable in such conditions. In this connection, there is an objective need for a systematic analysis and forecasting of measures taken to protect the domestic food market.The article outlines the main directions of the state economic policy of the Russian Federation. The main factors influencing the rise in food prices have been identified. These factors include an increase in the cost of the production cycle of crops and livestock due to import dependence, disruption of supply chains, mandatory labeling of certain goods, an increase in the price of mineral fertilizers, an increase in electricity tariffs and packaging costs, the exhaustion of limits on preferential loans to agricultural producers, an increase in world prices for food products deterioration of natural and climatic conditions.The level of self-sufficiency in basic foodstuffs and the main factors of growth in food prices have been considered. In addition, food inflation in the Russian Federation has been studied.Particular attention is paid to the measures taken by the Government that will help stabilize prices for important agricultural products and thereby ensure the country's food security: a temporary ban on the export of sunflower and rapeseed seeds; a quota for deliveries abroad of sunflower oil and cake, as well as solid residues from sunflower seeds; limiting the number of checkpoints for the export of soybeans and soybean meal from Russia; introduction of duties on the export of sunflower meal and oilseed flax.The purpose of the research is to study the measures taken by the Government to protect the domestic food market and stabilize prices for important agricultural products, as well as to identify the main factors affecting the rise in food prices.This study was conducted using the methods of statistical analysis, synthesis, comparison and deductive method.